A calibration facility for automatic weather stations. (16th November 2015) - Lopardo, G.; Bellagarda, S.; Bertiglia, F.; Merlone, A.; Roggero, G.; Jandric, N.
ABSTRACT: Environmental monitoring by automatic weather stations (AWSs) is growing as a result of the increasing number and reliability of surface observations. In order to ensure data traceability and obtain more comprehensive data on the performance of AWSs, a new transportable calibration facility was manufactured at the Italian Institute of Metrology (INRiM) in the framework of the project MeteoMet. The facility is equipped with temperature and pressure reference sensors directly traceable to the International System of Units (SI) to obtain meteorological data with well‐documented calibration uncertainty. In this calibration system, temperature and pressure can be controlled simultaneously and independently so that all combinations over the ranges are possible. The nominal ranges are: absolute pressure 50 to 110 kPa and temperature −25 to 50 °C. The availability of a large range of atmospheric variability and the possibility of studying the mutual influence effects on sensors response are important characteristics of the facility. This apparatus is also designed to permit a control in humidity, in order to complete the characterization of the whole AWS pressure–temperature–humidity modulus. As a matter of fact, the final version of the facility will be equipped with a humidity generator for hygrometer calibrations. Finally, the calibration system is designed to be transportable, therefore allowing the calibration of AWSs located at sites that are difficult to access such as Ny‐Ålesund (Svalbard) stations, where the facility was employed. The design and the technical characteristics are reported in this paper.